Whole exome sequencing and single nucleotide polymorphism array analyses to identify germline alterations in genes associated with testosterone metabolism in a patient with androgen insensitivity syndrome and early‐onset colorectal cancer. Issue 1 (7th June 2016) - Disciglio, Vittoria; Devecchi, Andrea; Palumbo, Orazio; Carella, Massimo; Penso, Donata; Milione, Massimo; Valle, Giorgio; Pierotti, Marco Alessandro; Vitellaro, Marco; Bertario, Lucio; Canevari, Silvana; Signoroni, Stefano; et al.
Abstract: Background: Androgen insensitivity syndrome (AIS), a disorder of sexual development in 46, XY individuals, is caused by loss‐of‐function mutations in the androgen receptor ( AR ) gene. A variety of tumors have been reported in association with AIS, but no cases with colorectal cancer (CRC) have been described. Case presentation: Here, we present a male patient with AIS who developed multiple early‐onset CRCs and his pedigree. His first cousin was diagnosed with AIS and harbored the same AR gene mutation, but with no signs of CRC. The difference in clinical management for the two patients was that testosterone treatment was given to the proband for a much longer time compared with the cousin. The CRC family history was negative, and no germline mutations in well‐known CRC‐related genes were identified. A single nucleotide polymorphism array revealed a microduplication on chromosome 22q11.22 that encompassed a microRNA potentially related to CRC pathogenesis. In the proband, whole exome sequencing identified a polymorphism in an oncogene and 13 rare loss‐of‐function variants, of which two were in CRC‐related genes and four were in genes associated with other human cancers. Conclusions: By pathway analysis, all inherited germline genetic events were connected in a unique network whose alteration in the proband, together with continuous testosterone stimulation, may have played a role in CRC pathogenesis.